Disentangling the Relationship Between Urinary Metal Exposure and Osteoporosis Risk Across a Broad Population: A Comprehensive Supervised and Unsupervised Analysis - Jianing Liu; Kai Wang (Toxics)
Background: Limited evidence links urinary metal exposure to osteoporosis in broad populations, prompting this study to cover this knowledge gap using supervised and unsupervised approaches. Methods: This study included 15,923 participants from the National Health and Nutrition Examination Survey (NHANES) spanning from 1999 to 2020. Urinary concentrations of nine metals—barium (Ba), cadmium (Cd), cobalt (Co), cesium (Cs), molybdenum (Mo), lead (Pb), antimony (Sb), thallium (Tl), and tungsten (Tu)—were measured using inductively coupled plasma mass spectrometry (ICP-MS). Osteoporosis was assessed via dual-energy X-ray absorptiometry. A weighted quantile sum (WQS) regression analysis evaluated each metal’s contribution to osteoporosis risk. Partitioning around medoids (PAM) clustering identified the high- and low-exposure groups, and their association with the risk and prognosis of osteoporosis was evaluated. Results: WQS regression identified Cd as a significant osteoporosis risk factor in the general population (odds ratio (OR) = 1.19, 95% confidence interval (CI): 1.08, 1.31, weight = 0.66). Pb notably affected those individuals aged 30–49 years and classified as Mexican American, while Sb impacted Black individuals. PAM clustering showed that the high-exposure group had a significantly higher risk of osteoporosis (OR = 1.74, 95% CI: 1.43, 2.12) and cumulative mortality risk. Conclusions: Urinary metals are associated with the risk and prognosis of osteoporosis.